Pengaruh Fasilitas Kerja, Motivasi Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Perusahaan Umum Daerah Air Minum Tirta Dhaha Kota Kediri - Natalia, Desy; Kurniawati, Endah; Hendratmoko, Suseno (Cahaya Ilmu Bangsa, 2025)
This study aims to determine the Influence of Work Facilities, Work Motivation, and Work Discipline on Performance at the Regional Public Drinking Water Company Tirta Dhaha, Kediri City. The analysis techniques used are validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis tests, and determination coefficient tests. The sample in this study was 83 respondents and used saturated samples for sampling. The results of the study indicate that Work Facilities have a significant effect on Employee Performance with a calculated t value (3.923)> t table (1.664) and a sig. value of 0.000 <0.05, Work Motivation has a significant effect on Employee Performance with a calculated t value (4.681)> t table (1.664) and a sig. value of 0.000 <0.05, Work Discipline has a significant effect on Employee Performance with a calculated t value (22.424)> t table (1.664) and a sig. value. 0.000 < 0.05, and Work Facilities, Work Motivation, and Work Discipline simultaneously have a significant effect on Employee Performance with a calculated F value (229.135) > F table (2.720) and a sig. value of 0.000 < 0.05